2016
DOI: 10.1007/s13201-016-0508-y
|View full text |Cite
|
Sign up to set email alerts
|

A method of groundwater quality assessment based on fuzzy network-CANFIS and geographic information system (GIS)

Abstract: The process of water quality testing is money/-time-consuming, quite important and difficult stage for routine measurements. Therefore, use of models has become commonplace in simulating water quality. In this study, the coactive neuro-fuzzy inference system (CAN-FIS) was used to simulate groundwater quality. Further, geographic information system (GIS) was used as the preprocessor and post-processor tool to demonstrate spatial variation of groundwater quality. All important factors were quantified and groundw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
12
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 51 publications
(12 citation statements)
references
References 62 publications
0
12
0
Order By: Relevance
“…Gholami et al [ 34 ] presented an advanced form of the ANFIS model for groundwater quality simulation; the proposed model was described as coactive-ANFIS (CANFIS) integrated with geographic information system (GIS). The training and validation of the proposed model was performed by considering a case study of Mazandaran Plain in the northern region of Iran.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Gholami et al [ 34 ] presented an advanced form of the ANFIS model for groundwater quality simulation; the proposed model was described as coactive-ANFIS (CANFIS) integrated with geographic information system (GIS). The training and validation of the proposed model was performed by considering a case study of Mazandaran Plain in the northern region of Iran.…”
Section: Introductionmentioning
confidence: 99%
“…The study also showed that the SVM model is a fast, reliable, and cost-effective AI technique. The feasibility of AI techniques in groundwater quality simulation has been evaluated by numerous scholars and such studies have produced efficient performances [32][33][34][35][36][37][38][39][40].…”
Section: Introductionmentioning
confidence: 99%
“…Researchers propose some CANFIS models (e.g. Parthiban and Subramanian, 2008;Aytek, 2009;Gholami et al, 2017), but they are specific to other studies framework that is different from this one. Besides, their code is not available.…”
Section: The Selected Ai-based Forecasting Models Evaluation and Resultsmentioning
confidence: 99%
“…In this way, application of the nonlinear regression is in preparation of SRCs during the flooding periods (Ferguson 1986;Phillips et al 1999;Holtschlag 2001;Peng and Zhou 2011;Fan et al 2012). Also, recently it has been developed several deterministic models to estimate the sediment production of the watersheds such as neurofuzzy, artificial neural network (ANN), dendritic regression, and genetic algorithm methods (Asselman 2000;Horowitz 2003;Abrishamchi et al 2005;Schluter et al 2005;Stefan and Andrew 2008;Gholami et al 2017Gholami et al , 2018. Yang et al (2009) found that for estimating total bed material sediment load in rivers, it is better to use the formulas based on physical laws of sediment transport, like those formulas that were developed based on power concept.…”
Section: Introductionmentioning
confidence: 99%